I probably have a closer relationship with my internet provider: Experiences of belonging (or not) among mature-aged regional and remote university students - Crawford, Nicole; Emery, Sherridan; Allen, Penny; Baird, Allen (Journal of University Teaching and Learning Practice, 2022)
While fostering a sense of belonging among university students is an objective of many universities, the landscape of belonging is complex and multifaceted. It is worthy of deeper interrogation, particularly for “non-traditional” students. This article draws on data from a national mixed-methods study that explored proactive ways of supporting the mental wellbeing of mature-aged students in regional and remote Australia. One of the overarching findings was students feeling invisible, misunderstood and undervalued. While this theme was relevant for many participants, it was also the case that other participants reported feeling visible, known and a sense of belonging. These inconsistencies prompted us to conduct further analyses of the quantitative and qualitative data, which were collected from a cross-sectional online survey of 1,879 mature-aged undergraduate students in regional and remote Australia and 51 interviews. We employed Yuval-Davis’s analytical framework for the study of belonging. In the quantitative analyses, several variables were found to have a significant association with inclusion/connection/belonging. They included: study mode; socio-economic status; having a diagnosed mental health condition; and supports. In the qualitative analysis, we explored students’ experiences in greater depth to gain insights into why some students experience belonging and others do not. Connections and relationships with university staff; familiarity with university systems and places; and feeling included and “part of” a subject/course/campus manifested in students feeling understood, known and a sense of belonging. Due to certain entrenched institutional approaches, in many cases, students’ experiences fell short of the supportive and caring learning communities that pedagogical approaches advocate.